Pengaruh Kecanduan Game Online Terhadap Perilaku Sosial Remaja di Wilayah Kelurahan Ciracas Jakarta Timur - Aisyah Fathul Jannah; Syaripulloh; Iwan Purwanto; Ulfah Fajarini (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
The increase in online gaming among adolescents has an impact on social aspects, including direct social interaction, empathy, and social control. However, empirical studies on the extent of the influence of online gaming addiction on adolescent social behavior in the local context are still limited. This study aims to determine the effect of online game addiction on the social behavior of adolescents in Ciracas Village, East Jakarta. This study uses a quantitative approach with a survey method and simple linear regression analysis technique. The sample in this study consisted of 100 adolescents selected using purposive sampling. The instrument used was a questionnaire with indicators referring to aspects of online game addiction according to Groves and the concept of social action according to Max Weber. The results of the analysis show that there is a significant influence between online game addiction and adolescent social behavior with a coefficient of determination of 92.4%. This indicates that a higher level of online game addiction is associated with lower levels of social behavior quality. These results support the notion that excessive online gaming may hinder the development of adolescents’ social identity and lead to dependency on the virtual world. The study is expected to provide useful insights for parents, educators, and policymakers in designing monitoring strategies and digital education that encourage adolescents to use technology wisely and maintain balance in their daily lives Keywords: Online Game Addiction, Social Behavior, Adolescents, Social Interaction, Social Action